Optimization of the in situ transesterification step for biodiesel production using biomass of Yarrowia lipolytica NCIM 3589 grown on waste cooking oil - Katre, Gouri; Raskar, Shubham; Zinjarde, Smita; Kumar, V. Ravi; Kulkarni, B. D.; RaviKumar, Ameeta (Energy, 2018)
The in situ (one-step) acid-catalyzed transesterification step for conversion to biodiesel of biomass from oleaginous yeast Yarrowia lipolytica grown on waste cooking oil (WCO) is studied. The process yield of biodiesel was optimized by investigating effects of various parameters, namely, biomass, methanol, chloroform, catalyst, temperature, time and sonication. A Plackett-Burman statistical design of experiments revealed that biomass is the most significant factor influencing biodiesel (FAME, fatty acid methyl ester) production. Subsequently, a one variable design (OVD) of experiments for increased biomass loadings showed higher yields of FAME with no additional requirement of reactants, solvents or special equipment. The biomass grown on WCO had a lipid productivity of 0.042 g L-1 h(-1) and 4 g of this loading gave a high FAME yield of 0.88 gin 8 hat 50 degrees C with methanol: chloroform (10:1) and acid catalyst (0.2 M H2SO4,1.0 ml g(-1)). The FAME profile had desirable amounts of saturated (32.81%), monounsaturated (36.41%), polyunsaturated (30.59%) methyl esters. The predicted and experimentally determined physico-chemical properties of FAME were found in accordance with specified international standards. Thus, the direct one-pot in situ transesterification reaction using Y. lipolytica biomass grown on WCO provides a high yield of biodiesel with potential applicability while simultaneously addressing the management of this pollutant. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Biodiesel; FAME; In situ transesterification; One -step; Waste cooking oil; Yarrowia lipolytica